Carbon offset management : worth considering when investing for reforestation CDM - Eriksson, Arvid (SLU/Dept. of Forest Products, 2010)
The idea for this project was initiated together with one of the leaders in the forest, paper and packaging industry. To get through an A/R CDM process the company is exposed to the risk of failing the process or that the overall costs will exceed the benefits of the project. This would delete the incentives to invest in GHG removals compared to purchasing emission allowances on the carbon market.